A systematic review of how studies describe educational interventions for evidence-based practice: stage 1 of the development of a reporting guideline - Phillips, Anna C; Lewis, Lucy K; McEvoy, Maureen P; Galipeau, James; Glasziou, Paul; Hammick, Marilyn; Moher, David; Tilson, Julie K; Williams, Marie T (Université d'Ottawa | University of Ottawa, 2014)
Abstract Background The aim of this systematic review was to identify which information is included when reporting educational interventions used to facilitate foundational skills and knowledge of evidence-based practice (EBP) training for health professionals. This systematic review comprised the first stage in the three stage development process for a reporting guideline for educational interventions for EBP. Methods The review question was ‘What information has been reported when describing educational interventions targeting foundational evidence-based practice knowledge and skills?’ MEDLINE, Academic Search Premier, ERIC, CINAHL, Scopus, Embase, Informit health, Cochrane Library and Web of Science databases were searched from inception until October - December 2011. Randomised and non-randomised controlled trials reporting original data on educational interventions specific to developing foundational knowledge and skills of evidence-based practice were included. Studies were not appraised for methodological bias, however, reporting frequency and item commonality were compared between a random selection of studies included in the systematic review and a random selection of studies excluded as they were not controlled trials. Twenty-five data items were extracted by two independent reviewers (consistency > 90%). Results Sixty-one studies met the inclusion criteria (n = 29 randomised, n = 32 non-randomised). The most consistently reported items were the learner’s stage of training, professional discipline and the evaluation methods used (100%). The least consistently reported items were the instructor(s) previous teaching experience (n = 8, 13%), and student effort outside face to face contact (n = 1, 2%). Conclusion This systematic review demonstrates inconsistencies in describing educational interventions for EBP in randomised and non-randomised trials. To enable educational interventions to be replicable and comparable, improvements in the reporting for educational interventions for EBP are required. In the absence of a specific reporting guideline, there are a range of items which are reported with variable frequency. Identifying the important items for describing educational interventions for facilitating foundational knowledge and skills in EBP remains to be determined. The findings of this systematic review will be used to inform the next stage in the development of a reporting guideline for educational interventions for EBP.